Use of crushed eggshell to control tomato blossom-end rot (Research, Society and Development, 2024)
Studies that attempt to control blossom-end rot in tomatoes using crushed eggshells as a source of calcium are rare. This study therefore aimed to control blossom-end rot in tomatoes with a solution obtained from eggshells. The eggshell used was dried, finely crushed and sieved in a 0.30 mm sieve. The treatments consisted of different concentrations of eggshell: 0.0, 0.6, 1.2, 2.4, 3.0, 6.0, 12.0, 24.0 and 40.0%. Each concentration of eggshell was diluted in boiling distilled water. After 24 h, the eggshell solutions were strained. In a preliminary assay, under laboratory conditions, the pH and electrical conductivity of these solutions were measured every 10 days for a maximum period of 30 days. The solutions were then sprayed on the aerial part, at 44 days after transplanting (DAT) of tomato plants, which had been arranged under field conditions, in pots of 22 kg of soil. The experiment was arranged in a randomized block design with four replications. At 84 DAT, growth and production indicators were evaluated. While the electrical conductivity of eggshell solutions increased with storage time, the pH values decreased. Tomato plants sprayed with the eggshell solution accumulated a lot of calcium in the aerial part and did not show blossom-end rot on their fruits. On the other hand, tomato plants sprayed with only distilled water showed the blossom-end rot in 15% of their fruits. Plants sprayed with eggshell solution showed even higher fruit fresh mass and higher branch dry mass. These results indicate that the eggshell solution inhibits the blossom-end rot in tomato.